2017
DOI: 10.1002/cncy.21859
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features and clinical implications of undifferentiated carcinoma with osteoclastic giant cells of the pancreas: An analysis of 15 cases

Abstract: The 3 classical UOC cell types are identifiable on FNA, making cytologic diagnosis possible if considered in the differential. A PDAC component is often also observed. The survival advantage of UOC over pure PDAC appears to be negated by FNA and requires further investigation. Cancer Cytopathol 2017;125:563-75. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…Undifferentiated pancreatic carcinoma with osteoclastic giant cells, formerly named pleomorphic carcinoma of the pancreas, giant cell carcinoma and sarcomatoid carcinoma, could briefly be included in the differential diagnosis due to the presence of pleomorphic tumor cells. In a study by Reid et al, three cell types (osteoclastic giant cells, pleomorphic tumor giant cells, and spindle/histiocytoid cells) were present in 12/15 cytology specimens . An important finding in 73% of their cases was the presence of pancreatic ductal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Undifferentiated pancreatic carcinoma with osteoclastic giant cells, formerly named pleomorphic carcinoma of the pancreas, giant cell carcinoma and sarcomatoid carcinoma, could briefly be included in the differential diagnosis due to the presence of pleomorphic tumor cells. In a study by Reid et al, three cell types (osteoclastic giant cells, pleomorphic tumor giant cells, and spindle/histiocytoid cells) were present in 12/15 cytology specimens . An important finding in 73% of their cases was the presence of pancreatic ductal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…The evidence suggests that the mononuclear cells in ORUCUT represent the neoplastic cells and the association of these tumors with in situ or high-grade papillary urothelial carcinoma in all six cases supported an epithelial origin. In addition, giant cell tumors in other visceral organs, such as the pancreas, have demonstrated robust epithelial staining in the mononuclear cells [14]. To further assess the histopathogenesis of ORUCUT, this study utilizes the more specific urothelial markers of GATA3, uroplakin II, and thrombomodulin.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of epithelial-mesenchymal transition (EMT), epithelial cells lose polarity and intercellular cohesion to adopt a mesenchymal, fibroblast-like, single-cell migratory phenotype. 13 Although some studies have reported cytopathological features of PAC, [14][15][16] immunocytochemical (ICC) findings including EMT markers have been sparsely investigated. According to previous reports, loss of E-cadherin and gain of vimentin are considered as hallmarks of EMT and the expressions of vimentin, E-cadherin, and zinc finger E-box binding homeobox 1 (ZEB1) in PDAC represent important prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In particular, recent reports suggest ZEB1 links EMT-activation and stem cell-maintenance by suppressing stem cellinhibiting microRNAs (miRNAs), and therefore, is a promoter of mobile, migrating cancer stem cells in pancreatic tumors. 13 Although some studies have reported cytopathological features of PAC, [14][15][16] immunocytochemical (ICC) findings including EMT markers have been sparsely investigated. We report an autopsy case of PAC on cytopathological characteristics and ICC findings, focusing on the expression of EMT markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation